The Oversight of the Constitutionality of Laws in the Jordanian Political System: A ‎Comparative Study - Al-Btoosh, Ayman Muhammad; Mubaideen, Rasha Adnan (Dirasat: Human and Social Sciences, 2025)
Objectives: As a comparative study, the current article aims to identify the extent to which the constitutionality of laws is applied in the Jordanian political system, by reviewing the types of oversight, as represented in the political and judicial domains. It also probes the constitutionality of laws in the Jordanian political system based on the constitutional amendments of (2011), which led to the creation of the Constitutional Court. Methods: The methodology adopted in this study is based on the descriptive approach. Results: The findings indicate cases of unconstitutionality of legal legislation, based on examining the approach followed to determine the extent to which the constitutionality of laws is applied in the political systems in the US and the Republic of France at the international level, and in Egypt at the regional level. The results are also drawn by analyzing the extent of compatibility between the constitutionality of laws at the international and regional levels on the one hand and within the Jordanian political system on the other. Conclusions: The research paper concludes with the most important issues and recommendations related to the current research problem by stating that rulings issued by the Constitutional Court are absolute, as opposed to relative, and are not subject to appeal. It also concludes that the ruling of unconstitutionality applies immediately, without having a retroactive effect.